The effect of Humor Training to Teacher on Academic Burnout in Students - Sama Sadat (پژوهشنامه روانشناسی مثبت, 2019)
Abstract The aim of this study was to determine the effect of humor training to teacher on academic burnout in students. To achieve the goal of research, the semi-experimental method including pre-test and post-test design were applied. For sampling, two classes selected out of sixth grade girl students in Tehran (zone 1), by multistage cluster sampling. Then one class as a control group (33 students) and another as an experimental group (33 students) were randomly selected. Academic Burnout Questionnaire (Salmela-Aro & Naatanen) completed by both group. Then humor training program was held through 4 sessions (3 hour per session) for teacher of the experimental group but teacher of the control group did not get training. Finally, Academic Burnout Questionnaire completed by both groups. To analyze the obtained data, ANCOVA was applied. The results showed that there was a significant difference between the groups. The academic burnout decreased in students of experimental group. Therefore, the article says that humor training to teachers can be used as an efficient way to decrease academic burnout in students.